Developing retroperitoneal anaplastic carcinoma with choriocarcinoma focus after ovarian non-gestastional choriocarcinoma: Case report - Nikolić Branka; Ljubić Aleksandar; Terzić Milan; Aranđelović Aleksandra; Babić Srđan; Vučić Miloš (Vojnosanitetski Pregled)
Introduction. Choriocarcinoma is a malignant form of gestational trophoblastic neoplasm (GTN). It is a rare event but also a curable malignancy. In the majority of instancies it developes after any gestational event. In some cases it developes as non-gestational extrauterine malignancy. Prognosis of choriocarcinoma is poor when invasion and metastases appear early and spread fast. This form of choriocarcinoma can lead to incurable and letal outcome. Case report. We presented a 20-year-old patient with abdominal and retroperitoneal malignancy - anaplastic carcinoma combined with choriocarcinoma metastases in. Tumor developed three months after left adnexectomy which had been done because of adnexal tumor. Choriocarcinoma was immunohistochemicaly confirmed in adnexal masses. Two courses of chemotherapy, metotrexate + folic acid (MTX+FA) regimen, were administrated. The initial serum beta human chorionic gonadotropin level stayed unknown as well as the last one after the treatment. The patient came from the other country and was hospitalized because of pelvic and abdominal pain and palpable abdominal masses in hypogastrium with progressive anemia. The human chorionic gonadotropin level was 38 mIU/L. Tumor biopsy was done and choriocarcinoma metastases were immunohistochemicaly confirmed with predominant anaplastic carcinoma. Five day course of MTX + cyclophosphamide regimen was administrated and the patient was prepared for operative treatment. Relaparotomy was perforemed and tumor completely exceeded. Tumor mass mostly developed retroperitonely and partialy in abdominal cavity infiltrating intestinal wall with rupture of sigmoid colon. Anaplastic carcinoma, with large fields of necrosis and bleeding, was confirmed after histological examination. Immunohistochemical examination excluded choriocarcinoma in tumor mass. After 20 blood units transfusion, one course of chemotherapy and tumor excision, the patient left hospital on the 9th postoperative day. The patient rejected chemotherapy which was recommended according to the protocol and died one month after the operation. Conclusion. Non-gestational metastatic choriocarcinoma complicated with another type of malignancy with early spread of the disease and low responsiriness to chemotherapy has poor prognosis and leads to lethal outocome. [Acknowledgment. Projekat Ministarstva nauke Republike Srbije, br. 41021 and 175082]